Attenuation of microRNA‐16 derepresses the cyclins D1, D2 and E1 to provoke cardiomyocyte hypertrophy. Issue 3 (13th January 2015) - Huang, Shuai; Zou, Xiao; Zhu, Jie‐Ning; Fu, Yong‐Heng; Lin, Qiu‐Xiong; Liang, Ye‐You; Deng, Chun‐Yu; Kuang, Su‐Juan; Zhang, Meng‐Zhen; Liao, Yu‐Lin; Zheng, Xi‐Long; Yu, Xi‐Yong; et al.
Abstract Cyclins/retinoblastoma protein (pRb) pathway participates in cardiomyocyte hypertrophy. MicroRNAs (miRNAs), the endogenous small non‐coding RNAs, were recognized to play significant roles in cardiac hypertrophy. But, it remains unknown whether cyclin/Rb pathway is modulated by miRNAs during cardiac hypertrophy. This study investigates the potential role of microRNA‐16 (miR‐16) in modulating cyclin/Rb pathway during cardiomyocyte hypertrophy. An animal model of hypertrophy was established in a rat with abdominal aortic constriction (AAC), and in a mouse with transverse aortic constriction (TAC) and in a mouse with subcutaneous injection of phenylephrine (PE) respectively. In addition, a cell model of hypertrophy was also achieved based on PE‐promoted neonatal rat ventricular cardiomyocyte and based on Ang‐II‐induced neonatal mouse ventricular cardiomyocyte respectively. We demonstrated that miR‐16 expression was markedly decreased in hypertrophic myocardium and hypertrophic cardiomyocytes in rats and mice. Overexpression of miR‐16 suppressed rat cardiac hypertrophy and hypertrophic phenotype of cultured cardiomyocytes, and inhibition of miR‐16 induced a hypertrophic phenotype in cardiomyocytes. Expressions of cyclins D1, D2 and E1, and the phosphorylated pRb were increased in hypertrophic myocardium and hypertrophic cardiomyocytes, but could be reversed by enforced expression of miR‐16. Cyclins D1, D2 and E1, not pRb, were further validated to be modulated post‐transcriptionally by miR‐16. In addition, the signal transducer and activator of transcription‐3 and c‐Myc were activated during myocardial hypertrophy, and inhibitions of them prevented miR‐16 attenuation. Therefore, attenuation of miR‐16 provoke cardiomyocyte hypertrophy via derepressing the cyclins D1, D2 and E1, and activating cyclin/Rb pathway, revealing that miR‐16 might be a target to manage cardiac hypertrophy.